Profile of poisoning cases among females: A 5-year retrospective study from poison detection centre of a tertiary care hospital - Ali, Kashif; Pujar, Somashekhar S; Honnungar , Ravindra S; Jirli, Prasanna S; Koulapur , Vishal V; Azizuddin Junaidi, Khaja; Pushpa, M G (Journal of Indian Academy of Forensic Medicine, 2019)
Poisoning is a serious problem throughout the world that could be suicidal, homicidal or accidental. In India more than 50,000 people  are dying every year from the exposure of poisonous compounds. In a developing country like India there is expansion of industrial  and agricultural fields on a large scale which gives rise to more production of insecticides and its accessibility thereby increasing its  exposure and toxicity. The objective of this study is to analyze the profile of Poisoning cases in females tested in Poison Detection  Centre of a tertiary care hospital over a period of 5 years. It is a retrospective record-based study of all poisoning samples of females  sent for analyzing to Poison Detection Centre (PDC) of KLE hospital, Belagavi from January 2012 to December 2016. The data  regarding pattern of poisoning, age, occupation and basic demographics were collected from hospital records.The study included total  380 female cases of which 334 were positive for various poisonous compounds and 46 were negative for standards tested. The  commonest age group was 19-29 years. Organophosphorus was commonest compound and least was Amitraz. The maximum number  of cases reported were among illiterate and were from rural background involved in agricultural activities. The maximum deaths were  seen with Organophosphorus compound. It is the need of hour to conduct health and poison awareness programs to keep a check on  increasing rate of poisoning cases.
Keywords: Poisoning; Poison Detection Centre; Females; Rural